2018
DOI: 10.1159/000494132
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Immediate versus Delayed Umbilical Cord Clamping in Multiple-Birth Infants Born Preterm

Abstract: Background: Delayed cord clamping (DCC) improves placental transfusion and increases blood volume in preterm infants when compared with immediate cord clamping (ICC). However, evidence to support DCC in multiple-birth preterm infants is still lacking. Objective: To compare the outcomes of ICC versus DCC in preterm infants of multiple births. Study Design: Women with a multiple pregnancy, including twins and triplets with a gestational age of 28–36 weeks, were randomized to receive ICC (23 women and 50 infants)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 21 publications
0
36
0
2
Order By: Relevance
“…With our review, we add new information, because we identified and included 11 additional recently published trials. [25][26][27][28][29][30][31][32][33][34][35] Although previous reviews included preterm infants born at less than 37 weeks' gestational age, 4,8 our review is limited to infants born at less than 34 weeks'. Although late preterm infants have increased risk for admission to neonatal intensive care and poor developmental outcome compared with term infants, they do not have the same serious morbidities experienced by less mature preterm infants.…”
Section: Agreement and Disagreement With Previous Researchmentioning
confidence: 99%
“…With our review, we add new information, because we identified and included 11 additional recently published trials. [25][26][27][28][29][30][31][32][33][34][35] Although previous reviews included preterm infants born at less than 37 weeks' gestational age, 4,8 our review is limited to infants born at less than 34 weeks'. Although late preterm infants have increased risk for admission to neonatal intensive care and poor developmental outcome compared with term infants, they do not have the same serious morbidities experienced by less mature preterm infants.…”
Section: Agreement and Disagreement With Previous Researchmentioning
confidence: 99%
“…It makes sense to provide them with more of their own blood through placental transfusion at birth [51,52]. Studies of multiple births have demonstrated feasibility of providing OCM to twins and triplets [53,54]. Thus, multiple births should not be routinely excluded.…”
Section: Potential Fetal Risk Conditionsmentioning
confidence: 99%
“…Il existe peu de données sur la prise en charge du cordon chez les jumeaux prématurés, car elles se limitent à un seul ECR de faible envergure 17 (80 jumeaux, dont 55 issus de grossesses monochoriales) et à deux études de cohortes 18,19 . Une méta-analyse révèle qu'aucun des quatre essais incluant des jumeaux n'avait stratifié les résultats d'après ce paramètre 5 .…”
Section: Jumeaux Prématurés Dans La Période Néonataleunclassified